A collaborative approach to supporting communication in the assessment of decision-making capacity. Issue 11 (21st May 2016) - Zuscak, Simon John; Peisah, Carmelle; Ferguson, Alison
Abstract: Purpose: This paper explores the clinical implications of acquired communication disorders in decisional capacity. Discipline-specific contributions are discussed in a multidisciplinary context, with a specific focus on the role of speech and language pathologists (SLPs). Method: Key rehabilitation issues in determining decisional capacity are identified. The impact of communication impairment on capacity is discussed in light of the research literature relating to supportive communication and collaborative practice that respects human rights. Results: Guidelines are presented for professionals involved in the assessment of the decisional capacity of individuals with communication disorders of neurological origin. They guide an assessor through: assessing cognition, language and speech; determining preferred communication domains; and practical strategies and considerations for maximising communication. Conclusion: There is a dearth of guidelines available that deal with augmenting and supporting communication of individuals with acquired communication disorders of neurological origin when it comes to assessing legal decision-making capacity. Capacity assessment is a multidisciplinary realm, and the involvement of SLPs is key to maximising the decision-making capacity of these individuals. Implications for rehabilitation: All clinicians have an obligation to maximise client autonomy and participation in decision-making. Assessments of capacity should involve a general cognitive ability assessment, followed by a decision-specific assessment tool or question set for the decision facing the patient. The involvement of speech and language pathologists (SLPs) is key to assess and facilitate capacity determinations in instances of cognitive-communication disorder. Impairments in different aspects of auditory comprehension require different accommodations.